Low-Grade Endometrial Stromal Sarcoma with a Nodule-in-Nodule Appearance in Preoperative Magnetic Resonance Images - Mitsuhiro Nakamura; Ryusuke Murakami; Kaoru Abiko; Taito Miyamoto; Yoshimi Kitawaki; Ken Yamaguchi; Akihito Horie; Junzo Hamanishi; Eiji Kodoh; Tsukasa Baba; Aki Kido; Sachiko Minamiguchi; et al. (Case Reports in Obstetrics and Gynecology)
Low-grade endometrial stromal sarcoma (LG-ESS) is a rare malignant disease and demonstrates various patterns in preoperative imaging. Therefore, accurate diagnosis is important. Given its unique form, we report a case of LG-ESS with a nodule-in-nodule appearance on preoperative imaging. A 41-year-old woman was referred to our department for further examination of a 45 mm diameter uterine corpus mass. Preoperative magnetic resonance imaging (MRI) revealed several small nodules within a larger nodule. T2-weighted images showed moderate-to-high signal intensity with focal bands of low signal intensity in the small nodules. The patient underwent total abdominal hysterectomy and bilateral salpingo-oophorectomy. Histopathological findings of the small nodules showed densely concentrated endometrial stromal cells reminiscent of a proliferative phase endometrium with a concentric arrangement of small spiral arteriole-like vessels. The small nodules exhibited an expansile growth pattern and were surrounded by less densely concentrated endometrial stromal cells intermingled with the normal uterine myometrium. LG-ESS with smooth muscle differentiation and sex cord-like elements was partially observed. In summary, LG-ESS demonstrating a unique nodule-in-nodule appearance on preoperative imaging histopathologically comprised tumor cells of varying densities. Our current case suggests that preoperative diagnostic imaging with MRI may be useful.